Synthesis, Characterization, DNA Binding, and Photocleavage Activity of Oxorhenium (V) Complexes with α-Diimine and Quinoxaline Ligands - Christiana A. Mitsopoulou; Constantinos Dagas (Bioinorganic Chemistry and Applications)
The complex [ReOCl3pq] (1) (where pq = 2-(2′pyridyl)quinoxaline) has been synthesized and fully characterized by UV-Vis, FTIR, 1 and 2D NMR, and cyclic voltammetry (CV). The DNA-binding properties of the complex 1 as well as of the compounds [ReOCl3bpy] (2), [ReOCl3phen] (3), and pq (4) were investigated by UV-spectrophotometric (melting curves), CV (cyclic voltammetry), and viscosity measurements. Experimental data suggest that complex 1 intercalates into the DNA base pairs. Upon irradiation, complex 1 was found to promote the cleavage of plasmid pBR 322 DNA from supercoiled form I to nicked form II. The mechanism of the DNA cleavage by complex 1 was also investigated.